Financializing authoritarian capitalism: Chinese fintech and the institutional foundations of algorithmic governance - Julian Gruin (Finance and Society, 2019)
Digital credit scoring is driving a number of significant transformations in Chinese economy and society, catalyzing financial liberalization, deepening financial inclusion, and shifting economic power beyond the previously state-controlled commercial banking system. Yet the significance of financial technology is informed in turn by locally specific traditions of governance and regulation. This article critically interrogates the rise of Chinese fintech, reconceptualizing it as a process of financialization that is embedded in a Chinese systems- oriented authoritarian governance tradition. On the basis of documentary sources, Chinese- language secondary literature, and fieldwork conducted from 2016-18, it argues that in addition to disrupting existing practices of financial intermediation, the emergence of novel digital credit scoring technologies is enabling new forms of algorithmic governance to be exercised over the process of financialization, which in turn represents an important component in the construction of China's neo-statist authoritarian capitalism. These findings have broader implications for how we understand the importance of new financial technologies in an era of big data, contributing to contemporary debates in international political economy, economic sociology, and Chinese studies.
Keywords: 300; Authoritarian capitalism; China; digital credit scoring; technology; financialization; neo-statism